2020
DOI: 10.1186/s13054-020-03323-5
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 detection in the lower respiratory tract of invasively ventilated ARDS patients

Abstract: Background Data on SARS-CoV-2 load in lower respiratory tract (LRT) are scarce. Our objectives were to describe the viral shedding and the viral load in LRT and to determine their association with mortality in critically ill COVID-19 patients. Methods We conducted a binational study merging prospectively collected data from two COVID-19 reference centers in France and Switzerland. First, we described the viral shedding duration (i.e., time to negativity) in LRT samples. Second, we analyzed viral load in LRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
(28 reference statements)
0
19
0
1
Order By: Relevance
“…One of the potential consequences of immunosuppression is delayed SARS-CoV-2 RNA clearance [47], which had already been observed in SARS and MERS [6] but not observed in SARS-COV 2 patients [48]. In addition, the immunosuppression induced by steroids could also lead to a higher risk of superinfections [23,45].…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential consequences of immunosuppression is delayed SARS-CoV-2 RNA clearance [47], which had already been observed in SARS and MERS [6] but not observed in SARS-COV 2 patients [48]. In addition, the immunosuppression induced by steroids could also lead to a higher risk of superinfections [23,45].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of SARS-CoV-2, several antiviral drugs have been tested, but the effects on viral kinetics or even symptom evolution remain modest, even though promising results were recently found with monoclonal antibodies ( 43 ). It is also possible that viral replication in the lower respiratory tract (LRT) is a better predictor of outcome than nasopharyngeal viral load ( 44 ). Here our data showed a correlation between viral load values in both compartments ( SI Appendix , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We may hypothesize that evolution of COVID-19 toward increasing severity in this population of old patients is mainly a consequence of this altered immune status [ 32 – 35 ]. For example, previous studies showed the negative correlation between lymphocytes count and pulmonary viral load [ 36 , 37 ] while, elsewhere, the magnitude of pulmonary viral load was repeatedly associated with increased mortality [ 8 , 38 43 ]. In the present work, this is also illustrated by the association between nasopharyngeal viral load and increased mortality, SOFA and IL-6 levels upon admission.…”
Section: Discussionmentioning
confidence: 99%
“…First, it probably participates in the long duration necessary to eradicate SARS-CoV-2 from the lung in invasively ventilated patients as described elsewhere [ 43 ]. For example, it was shown that the viral shedding in lower respiratory tract lasted almost 30 days in median in critically ill COVID-19 patients [ 38 , 42 ]. Second, it most likely contributes to the very high rates of nosocomial infections reported not only in the present study (50%) but also in many others [ 26 , 27 , 45 ].…”
Section: Discussionmentioning
confidence: 99%